2021
DOI: 10.20944/preprints202107.0400.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pan-genome of Novel <em>Pantoea stewartii</em> subsp. <em>indologenes</em> Reveal Genes Involved in Onion Pathogenicity and Evidence of Lateral Gene Transfer

Abstract: Pantoea stewartii subsp. indologenes (Psi) is a causative agent of leafspot of foxtail millet and pearl millet; however, novel strains were recently identified that are pathogenic on onion. Our recent host range evaluation study identified two pathovars; P. stewartii subsp. indologenes pv. cepacicola pv. nov. and P. stewartii subsp. indologenes pv. setariae pv. nov. that are pathogenic on onion and millets or on millets only, respectively. In the current study we developed a pan-genome using the whole genome s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…P. stewartii subsp. indologenes was originally described as a pathogen of leaf spot on pearl millet (Pennisetum glaucum) and foxtail millet (Setaria italica) (Mergaert et al, 1993) but, since then, it has been found to cause disease on several additional plant species, including onion (Allium cepa) (Agarwal et al, 2021b;Koirala et al, 2021). P. stewartii subsp.…”
Section: Ecology Lifestyle and Biotechnological Usesmentioning
confidence: 99%
“…P. stewartii subsp. indologenes was originally described as a pathogen of leaf spot on pearl millet (Pennisetum glaucum) and foxtail millet (Setaria italica) (Mergaert et al, 1993) but, since then, it has been found to cause disease on several additional plant species, including onion (Allium cepa) (Agarwal et al, 2021b;Koirala et al, 2021). P. stewartii subsp.…”
Section: Ecology Lifestyle and Biotechnological Usesmentioning
confidence: 99%